Pendekatan ABCD dalam Upaya Peningkatan Jumlah Santri di Pondok Pesantren An-Nahdlah Kebumen - Astuti, Astuti; Chamidi, Agus Salim (IAINU Kebumen, 2025)
This article aims to find out about the ABCD approach in an effort to increase the number of student at the An-Nahdlah Kebumen Islamic Boarding School. The purpose of the research are: (1) to find out what are the best practice assets owned by the An-Nahdlah Kebumen Islamic boarding school to increase the number of students; (2) to find out how the process of increasing the number of students through product marketing at the An-Nahdlah Kebumen Islamic Boarding School usithe ABCD approach. The type of research used is qualitative research. The subject of the informants studied were the caretakers, ustadz and the administrators of the islamic boarding school. Data collection technique used observation, interviews, focus group discussion (FGD), and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of the research show that: An-Nahdlah Kebumen Islamic boarding school has various assets that include physical assets, human resources, social, culture, environment, finance, technology, digital networks, organizations, and time. Through the ABCD approach, these assets are mapped and optimized in the Discovery, Dream, Design, Define, and Destiny stages. In order to design and implement the right marketing strategy. The strategies implemented include media social, namely the creation of brochures, pamhlets, content by collaborating with campus media, the content media student activity unit, socialization of tahfidz programs through tahfidz on screen and qur’ani prayers. Evaluations are carried out periodically for the sustainability of the programs